ANALISIS STRATEGI PEMASARAN BUAH NAGA MENGGUNAKAN BAURAN PEMASARAN (MARKETING MIX) DAN SWOT - Rahma, Mulia Annisa; Heryansyah, Muh. Taufiek; Zahra, Farras Zalikhah; Irianto, Heru (LPPM Universitas Malikussaleh - Indonesia, 2023)
This research aims to 1) determine the marketing mix strategy of dragon fruits in UD Sabila Farm, and 2) analyze the marketing strategy for dragon fruit in UD Sabila Farm using the SWOT framework. The study was conducted at UD Sabila Farm, Kaliurang Street Km. 18.5, Kertodadi, Pakembinangun, Pakem Sub-district, Sleman District, Yogyakarta. The research employed a qualitative descriptive methode with a case study approach. The data were gathered through the process of observation, conducting in-depth interviews, and documentation. Based on the results, it was mentioned that the applied marketing mix includes the 7P of the marketing mix applied are price, promotion, place, product, people, process, and physical evidence. The SWOT analysis revealed internal factors encompassing strengths and weaknesses, as well as external factors involving opportunities and threats. Firstly, the strengths of UD Sabila Farm are the excellent Agroeduwisata concept, strategic location, and use of certified seeds. Second, the weaknesses are plant diseases and infections that cause fluctuating production, and they are unable to optimize social media. Furthermore, the opportunities include high demand and an existing market, while the threats of UD Sabila Farm include increased competition and a high number of imported products in the market.